Re-reading Shakespeare’s As You Like it through the Ecocritical Lens - Khan, Sadat Zaman (Literary Studies, 2023)
Shakespeare’s pastoral comedy As You Like It abounds with references to nature. This play portrays his bent towards nature, its (nature’s) protection and preservation. In his days, the concept of environmental degradation was not there because the evils of industrial pollution had not been realized the way it is now been. “Greenhouse Gas Emission” (EPA.gov., 2021) and the “carbon footprint” (N. Eckley, 2010) are some of the recent indicators of climate change, ponderously talked about and heavily weighed in scientific world, and in the academies. However, it is surprising that even in the sixteenth century Shakespeare had thought about ecology, nature as home for the animals and its protection. Was he eco-conscious? This might be an important question to Shakespeare enthusiast. This essay explores his concerns for ecology as the play focuses on the killing of the animals’ – deer as representative – in their “native dwelling places” (2.1.175)”, that is, the forest, and the “usurpation” (2.1.26) of the human being on its green spaces. Hence the essay re-reads Shakespeare’s As You Like It through the lens of ecocritical studies, inclusive of natural world and animals, in relation to the human world.